439 Epidemiology of ovarian cancer in kazakhstan (2013–2018). (4th December 2020) - Kaidarova, Dilyara; Kukubassov, Yerlan; Bolatbekova, Raikhan; Satanova, Alima
Abstract : Introduction/Background: Worldwide, ovarian cancer (OC) is the seventh most common cancer in women, with a five-year survival rate below 45%. Every year around the world, OC is diagnosed in 240, 000 women. Studies on the epidemiology of OC were carried out in different regions of the world, taking into account various factors. At the same time, the issues of the relationship between morbidity and mortality from OC with genetic, hormonal factors, as well as nutritional factors, morphometric factors, somatic pathology, socio-demographic and other factors were taken into account. The problem of OC epidemiology is extremely relevant for the Republic of Kazakhstan due to the significant prevalence of this disease among the female population, the still high level of neglected cases, as well as high mortality. Methodology: To analyze the epidemiological data of OC in the world, materials from the Globocan 2018 database of the International Agency for Research on Cancer (IARC) were used. To analyze the main statistical data for the regions of Kazakhstan, statistical data from the Cancer Register of the Republic of Kazakhstan for 2013–2018 were used. Results: In the Republic of Kazakhstan alone, there are more than 1000 new cases of OC and more than 400 deaths from this disease per year [5], while in the United States there are more than 22, 000 new cases of OC and 14, 000 deaths per year [6, 7]. In Kazakhstan, malignant neoplasms of the ovaries occupies the 3rd rank position among gynecological cancers. When analyzing rough intensive indicators of the incidence of ovarian cancer, there is an increase in the detection rate of this disease for the period from 2013 to 2018.[8–10] The analysis of age-related incidence rates showed that malignant neoplasms of the ovaries are found in all age groups, with a noticeable increase by 65–69 years. The main contingent of the sick are women of working age. Also, when analyzing this five-year period (2013–2018), there is a decrease in the incidence in childhood and adolescence, so in 2014, 5 cases of ovarian cancer were recorded in the age group 5–19 years, and in 2019 - 1 case of this disease. Over the past decade, there has been an increase in morbidity at the age of 55–65 years [5]. Conclusion: Morbidity and mortality from OC remain an urgent epidemiological problem in Kazakhstan and require further scientific research to identify risk factors. There are regions in the Republic of Kazakhstan that exceed the national average. In these regions, it is necessary to more widely apply modern methods of early diagnosis and treatment of ovarian cancer. If detected at earlier stages, it is possible to obtain significant results of OC treatment. The main tasks of OC epidemiology are: continuation of in-depth studies of the prevalence in the regions of the Republic of Kazakhstan with the identification of population groups and regions with the lowest and highest rates of morbidity and mortality from OC. Disclosures: Epidemiological data on the incidence rates of malignant neoplasms of the ovaries according to Globocan 2018 show significant differences across countries (per 100, 000 women): from 3.8 in Central Africa to 11.9 in Central and Eastern Europe [1].